Measuring Perseverance and Passion in Distance Education Students: Psychometric Properties of the Grit Questionnaire and Associations With Academic Performance - Xu, Kate M.; Meijs, Celeste; Gijselaers, Hieronymus J. M.; Neroni, Joyce; de Groot, Renate H. M. (Frontiers in Psychology, 2020)
With modern technological advances, distance education has become an increasingly important education delivery medium for, for example, the higher education provided by open universities. Amongst predictive factors of learning in distance education, the effects of non-cognitive skills are less explored. Grit, the dispositional tendency to sustain trait-level passion and long-term goals, has raised much research interest and gained importance for predicting academic achievement. The Grit Questionnaire, measuring Perseverance of Effort and Consistency of Interests, has been shown to be a reliable instrument in traditional university student populations. However, the measurement and predictive validity of this questionnaire is still unknown for adult distance education university students who differ from traditional students in various ways. Based on a sample of 2,027 students from a distance education university, this study demonstrated the psychometric validity of the two-factor structure grit measured by the Short Grit Questionnaire. Contrary to findings in traditional higher education settings, Perseverance of Effort was not associated with academic performance. Instead, higher Consistency of Interests positively predicted academic performance in terms of the number of courses completed. In particular, for female students the likelihood of attempting a course exam was positively predicted by Consistency of Interests. The findings suggest that Consistency of Interests a potentially useful factor to consider to improve learning performance for distance education, in particular for female students.